Is one share/one vote optimal? - Gromb, Denis; Acharya, Viral (Review of Finance, 2025)
Abstract In a tender offer by a value-increasing raider, voting shareholders face a free-rider problem. However, when they are not atomistic, they do not completely free-ride. In contrast, non-voting shareholders, who are never pivotal for the success of the offer, are absolute free-riders. Hence, in this case there is a gain from departing from one share/one vote. This departure also has a cost; there is an increased vulnerability to value-decreasing raiders, and the optimal governance structure balances the cost and the gain.